Short-latency responses in chronic ankle instability - Valente, I.M. (2017)
Ankle proprioceptive impairments after ankle sprain appear to be in the origin of the neuromuscular dysfunction in Chronic Ankle Instability (CAI), however the analysis of this condition has been focused on a unilateral approach. Considering that proprioceptive information have a determinant role in ipsilesional limb responses but also the contralesional ones, the present study aims to analyze the bilateral Short Latency Responses (SLR) in response to an unilateral perturbation in individuals with CAI. Two groups of athletes participated in the present study. One was composed by participants presenting CAI (CAI group, n = 16), while the other was composed by participants not presenting ankle sprain episodes (control group, n = 20). The electromyographic activity of the Peroneal Brevis and Longus (PB and PL), Tibialis Anterior (TA) and Soleus (SOL) muscles was collected during a unilateral sudden inversion perturbation in both the support and perturbed limbs. The timing of muscle activation of both limbs was used for analysis. Delayed SLR of TA (p = 0.009) and in SOL (p = 0.042) muscles were observed in the contralesional limb of the CAI group in the support position compared to the control group. In CAI group, delayed SLR of PB (p = 0.023) and SOL (p = 0.004) muscles was found in the contralesional limb in the support position compared to the ipsilesional one. The rehabilitation of individuals with CAI should also be focused on the contralesional limb while assuming a support position and also, contralesional limb should not be considered a reference for comparison between limbs.